Design and behavior analysis of prefabricated modular ferrocement floor slab system for interior application - Opon, Joel Galupo (Asia-Pacific Journal of Science, Mathematics, and Engineering, 2014)
This study was focused on creating an interior floor slab system that can be prefabricated in modular form out of ferrocement technology. The design of the system was outline using the mechanics of materials and the modified theory of plates in meeting the requirements of the local building and National Structural Codes (NSCP) including the American Concrete Institute (ACI) guide for ferrocement design. Results of the study have shown that ferrocement is an excellent and safe technology for an interior prefabricated modular slab design for economic reasons. However, it was important to strictly follow the methods outlined in the construction guide to achieve the require results.